2015
DOI: 10.3892/or.2015.3765
|View full text |Cite
|
Sign up to set email alerts
|

Capecitabine metronomic chemotherapy inhibits the proliferation of gastric cancer cells through anti-angiogenesis

Abstract: To evaluate the inhibitory effect and mechanism of capecitabine metronomic chemotherapy on gastric cancer cells. In vitro, the effects of 5-fluorouracil (Fu) metronomic chemotherapy on proliferation, apoptosis, tube formation ability, and angiogenesis were detected. In vivo, Ki-67, CD34 and VEGF were detected by immunohistochemical staining (IHC). Flow cytometry was used to detect the percentage of circulating endothelial progenitors (CEPs), and VEGF and PDGF were detected by ELISA in the peripheral blood of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 35 publications
5
18
0
1
Order By: Relevance
“…4B). These results correspond with those of our previous study revealing that it is 5-FU and capecitabine metronomic chemotherapy rather than 5-FU and capecitabine traditional chemotherapy that decrease the MVD in the GC xenografts (9). The mean densities of VEGF in the 5-Fu MTD, 5-Fu LDM, capecitabine MTD, capecitabine LDM and control groups were 0.016±0.001, 0.0066±0.0001, 0.063±0.001, 0.012±0.001, and 0.063±0.001, respectively (Fig.…”
Section: Effect Of Different Chemotherapy Patterns On the Expression supporting
confidence: 82%
See 4 more Smart Citations
“…4B). These results correspond with those of our previous study revealing that it is 5-FU and capecitabine metronomic chemotherapy rather than 5-FU and capecitabine traditional chemotherapy that decrease the MVD in the GC xenografts (9). The mean densities of VEGF in the 5-Fu MTD, 5-Fu LDM, capecitabine MTD, capecitabine LDM and control groups were 0.016±0.001, 0.0066±0.0001, 0.063±0.001, 0.012±0.001, and 0.063±0.001, respectively (Fig.…”
Section: Effect Of Different Chemotherapy Patterns On the Expression supporting
confidence: 82%
“…Our previous studies have confirmed that metronomic 5-Fu-based chemotherapy may perform an anti-angiogenetic role, which is associated with the antitumor effects of metronomic chemotherapy in vivo and in vitro. Compared with the conventional dose traditional chemotherapy, the antitumor effect of low dose metronomic chemotherapy is not inferior to the former (8,9). In addition to the anti-angiogenetic effect, it was speculated that there are other factors that enhance the antitumor effect of low-dose groups.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations